Capital Buffers as Determinants of Banking Sector Security: Empirical Analysis of Meeting the Combined Buffer Requirement - Chaikovska, Ivanna (Journal of Finance and Financial Law, 2021)
The purpose of the article. The purpose of the article is to assess the importance of capital buffers in ensuring the security of individual banks and the entire banking sector. This scientific study characterizes the amount of the buffer requirement, countercyclical buffer, systemic risk buffer, and buffer of other institutions of systemic importance in the Polish banking sector. In addition, an empirical analysis of the capital requirement was carried out, taking into account the combined buffer requirement and the total capital ratio in the Polish banking sector.Methodology. The calculations used financial data provided by the Polish Financial Supervision Authority and consolidated financial statements of Polish banks. To achieve the set goal, a methods of comparing documents and legal acts were used (especially in the part concerning the characteristics of capital buffers) and methods of descriptive statistics (in the empirical part of the subsection).Results of the research. The above analysis is the basis for answering the question whether post-crisis capital buffers increase the level of security of the Polish banking sector.